176k views
2 votes
Which of the following equations shows how substitution can be used to solve

the following system of equations?

Which of the following equations shows how substitution can be used to solve the following-example-1

1 Answer

2 votes

Answer: Choice B)

2x+5(2x+3) = 3

============================================

Reasoning:

We start with the second equation 2x+5y = 3

Since y = 2x+3 from the first equation, we can replace every copy of y with (2x+3). This replacement is valid because y and 2x+3 are the same.

So that's how we go from 2x+5y = 3 to 2x+5(2x+3) = 3

This replacement is done to get rid of the y variable, and it allows us to solve for x later on.

User Marshal Chen
by
5.8k points